Transcriptional Enhancer Factor Domain Family member 4 Exerts an Oncogenic Role in Hepatocellular Carcinoma by Hippo‐Independent Regulation of Heat Shock Protein 70 Family Members. Issue 4 (20th January 2021) - Coto‐Llerena, Mairene; Tosti, Nadia; Taha‐Mehlitz, Stephanie; Kancherla, Venkatesh; Paradiso, Viola; Gallon, John; Bianco, Gaia; Garofoli, Andrea; Ghosh, Souvik; Tang, Fengyuan; Ercan, Caner; Christofori, Gerhard M.; et al.
Abstract : Transcriptional enhancer factor domain family member 4 (TEAD4) is a downstream effector of the conserved Hippo signaling pathway, regulating the expression of genes involved in cell proliferation and differentiation. It is up‐regulated in several cancer types and is associated with metastasis and poor prognosis. However, its role in hepatocellular carcinoma (HCC) remains largely unexplored. Using data from The Cancer Genome Atlas, we found that TEAD4 was overexpressed in HCC and was associated with aggressive HCC features and worse outcome. Overexpression of TEAD4 significantly increased proliferation and migration rates in HCC cells in vitro as well as tumor growth in vivo . Additionally, RNA sequencing analysis of TEAD4 ‐overexpressing HCC cells demonstrated that TEAD4 overexpression was associated with the up‐regulation of genes involved in epithelial‐to‐mesenchymal transition, proliferation, and protein‐folding pathways. Among the most up‐regulated genes following TEAD4 overexpression were the 70‐kDa heat shock protein (HSP70) family members HSPA6 and HSPA1 A. Chromatin immunoprecipitation–quantitative real‐time polymerase chain reaction experiments demonstrated that TEAD4 regulates HSPA6 and HSPA1A expression by directly binding to their promoter and enhancer regions. The pharmacologic inhibition of HSP70 expression in TEAD4 ‐overexpressing cells reduced the effect of TEAD4 on cell proliferation. Finally, by overexpressing TEAD4 in yes‐associated protein ( YAP )/transcriptional coactivator with PDZ binding motif ( TAZ )‐knockdown HCC cells, we showed that the effect of TEAD4 on cell proliferation and its regulation of HSP70 expression does not require YAP and TAZ, the main effectors of the Hippo signaling pathway. Conclusion: A novel Hippo‐independent mechanism for TEAD4 promotes cell proliferation and tumor growth in HCC by directly regulating HSP70 family members. Abstract :